THE HUMORAL IMMUNITY RESPONSE OF DOG VACCINATED WITH ORAL SAG2 AND PARENTERAL RABISIN AND RABIVET SUPRA92 - -, Faizah; Mantik-Astawa, IN; Putra, AAG; -, Suwarno (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
ABSTRACT This research aims to determine whether SAG2 oral vaccine induced antibody response as high as that of parenteral vaccine (Rabisin and Rabivet Supra 92). The experimental design applied was randomized pre and post control group design with 4 treatments (oral SAG2 vaccine, parenteral rabisin, parenteral Rabivet Supra 92 and control without vaccination) and with 9 replication. As many as 36 kampung dogs used and the anti rabies antibody was determined by enzyme-linked immunosorbent assay (ELISA) at day 0, 21, 56, 84, 119, and 147 post vaccination. The antibody titer induced by oral SAG2 vaccine raised more slowly but persisted longer than parenteral vaccine. On day 21 after vaccination, the average antibody titers induced by oral SAG2 vaccines (0.501 IU/ml) was still significantly lower than those induced by parenteral Rabisin (3.504 IU/ml) and Rabivet Supra92 (2.545 IU/ml). However, by day 119 after vaccination the average antibody titer induced by SAG2 oral vaccine (0.889 IU/ml) was significantly higher (p <0.05) as compared to those of parenteral Rabisin (0.625 IU/ml) and Rabivet Supra 92 (0.223 IU/ml). The antibody response induced by SAG2 oral vaccine appears to persist longer than parenteral vaccines and it can therefore be used as an alternative vaccine to combat rabies in animals, especially for dogs kept in free range.